The Effect of Q-Switched Nd:YAG 1064 nm/532 nm Laser in the Treatment of Onychomycosis In Vivo - Kostas Kalokasidis; Meltem Onder; Myrto-Georgia Trakatelli; Bertrand Richert; Klaus Fritz (Hindawi Limited, 2013)
In this prospective clinical study, the Q-Switched Nd:YAG 1064 nm/532 nm laser (Light Age, Inc., Somerset, NJ, USA) was used on 131 onychomycosis subjects (94 females, 37 males; ages 18 to 68 years). Mycotic cultures were taken and fungus types were detected. The laser protocol included two sessions with a one-month interval. Treatment duration was approximately 15 minutes per session and patients were observed over a 3-month time period. Laser fluencies of 14 J/cm2 were applied at 9 billionths of a second pulse duration and at 5 Hz frequency. Follow-up was performed at 3 months with mycological cultures. Before and after digital photographs were taken. Adverse effects were recorded and all participants completed "self-evaluation questionnaires" rating their level of satisfaction. All subjects were well satisfied with the treatments, there were no noticeable side effects, and no significant differences were found treating men versus women. At the 3-month follow-up 95.42% of the patients were laboratory mycologically cured of fungal infection. This clinical study demonstrates that fungal nail infections can be effectively and safely treated with Q-Switched Nd:YAG 1064 nm/532 nm laser. It can also be combined with systemic oral antifungals providing more limited treatment time.